The Priority of Gathering in the Perspective of Hadith - Wilda Fauziah Rahman; Mulyana Mulyana (UIN Sunan Gunung Djati Bandung, 2021)
This study aims to discuss the importance of friendship from the hadith perspective. This research is a qualitative type through literature study with the hadith analysis method. The results and discussion of this research include the meaning of friendship, hadiths about friendship, and efforts to build friendship from hadith perspective. This study concludes that Gathering is a worship activity that has enormous virtues, both in the form of gifts in the world and rewards in the hereafter. Gathering has a very important meaning, especially in one's life and generally for Muslims as a whole. Gathering is a milestone that strengthens many things, from unity, care, compassion, and livelihood, making it easier for someone to enter heaven. If each individual is able to build good friendship, there will be many conveniences. Therefore, the vehicle for hospitality must always be built and preserved.